أثر حوكمة السياسة النقدية في الحد من ظاهرة التضخم في الجزائر - براهمي, فوزية; حديدي, آدم (جامعة الوادي - University of Eloued, 2022)
This studyaims to know the most important aspects of monetarypolicy and the application of the principles of governance in it, especially the principle of disclosure and transparency, for the governance of monetarypolicytools, especially quantitative tools, to find out if the governance of thosetoolscontributes to reducing the phenomenon of inflation in Algeria, the surveytoolwasusedthrough a questionnaire thatreflects The visions of specialists in thisfield, and the answerswereanalyzedusing the SPSS program, whose outputs support the application of monetarypolicygovernance in the decisions of the monetaryauthorityamongbanksbecause of their impact on reducing the phenomenon of inflation, and the governance of monetarypolicycontributes to a significant and noticeabledecrease in inflation rates whenapplied in the economy.
The impact of monetary policy governance on reducing inflation in Algeria
مقال
Keywords: السياسة النقدية، حوكمة السياسة النقدية، ظاهرة التضخم.